Mark Up, Bai` bi Tsaman Ajil dan Kredit menurut Manajeman Keuangan Islam - Mustofa Mustofa (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
This paper is aimed to provide a clear picture of differences in interest or usury and mark-up that has sometimes lead to miss-interpretation within community in a variety of banking transactions, especially on credit. The difference in price (mark up) in a murabahah transaction by Ã¢â‚¬Å“bai `bi tsaman ajilÃ¢â‚¬Â cannot be equated with loan transactions in conventional banks, if the mark up its credit determination based on changes in interest rates that apply to each bank and can be changed at any time based on changes in interest rates, and determination that is made unilaterally by the creditor without first bargaining with the debtor. While at Ã¢â‚¬Å“murabahan bai wa tsaman ajilÃ¢â‚¬Â, setting his mark up is made in advance at the time of the transaction and does not change until the end of the agreement.